SOCIODEMOGRAPHIC VARIATION AND ITS RELATION TO KNOWLEDGE ON PHYSICAL EXERCISE AMONG ACADEMIC STAFFS IN FACULTY OF MEDICINE, UITM, MALAYSIA - Rahman, Che Syahida Silmi Che Abdul; Al-Kubaisy, Waqar; Mustafah, Nadia Mohd; Rozali, Siti Nur Shakirah Mohd; Anuar, Fadzlin Najwa; Rahazi, Nurul Amirah Hannah; Adnan, Ahmad Aiman Mohd (LIFE: International Journal of Health and Life-Sciences, 2015)
Regular physical exercise is very important to maintain physical and mental health. Many studies were done showing importance of exercise. It is important to differentiate between physical activity and physical exercise especially for academic staffs of medical faculty to have an adequate knowledge to be implemented to the students. Thus, we have conducted this study to assess knowledge of physical exercise among academic staff of medical faculty and to determine the association between knowledge of physical exercise and socio-demographic profile, to determine whether the knowledge of physical exercise is differed between Medical Degree (MD) graduated and non-MD graduated. A cross sectional study was conducted during a period of 9 months from January to September 2015 in Faculty of Medicine, UiTM. Total of 220 well-structured self-responded questionnaires were distributed to the academic staff’s candidates. The questionnaires consist of two parts comprising socio-demographic profile and assessment of knowledge about physical exercise. The knowledge part consists of three domains that reflecting concept, type and recommended duration of physical exercise. Generally, only total of 22.6% respondents has good knowledge. Males showing significantly higher rate (47.7%) of good knowledge on concept of exercise than females (29.7%), while females were significantly has higher rate (55.9%) of good knowledge on types of physical exercise than males (36.4%). Similarly, married staffs also has a significantly higher rate (56.9%) of good knowledge on types of exercise compared to single/divorced staffs (34.8%). Clinical academic staffs has a significantly higher rate (13.1%) of good knowledge about recommended duration of physical exercise than preclinical academic staffs (2.1%). On the other hand, no significant differences between MD graduated or non-MD graduated staffs neither in overall knowledge, knowledge on concept, types or recommended duration of physical exercise. This study found that the knowledge on physical exercise among academic staffs of Faculty of Medicine, UiTM was poor. Males have s good knowledge on concept of physical exercise but females have a better knowledge on types of physical exercise as well as married staffs’ on types of physical exercise. On the other hand, clinical academic staffs has more knowledge on recommended duration of physical exercise.